2002
DOI: 10.1253/circj.66.1128
|View full text |Cite
|
Sign up to set email alerts
|

Use of Near-Infrared Spectroscopic Measurement at the Buttocks During Abdominal Aortic Surgery.

Abstract: uring abdominal aortic surgery, dynamic changes occur in the circulation of the pelvic area, but until now there was no method of evaluating them. Recently, near-infrared spectroscopy (NIRS) 1 has been used to evaluate muscle deoxygenation 2,3 and various vascular diseases, 4-7 including intermittent claudication accompanying arteriosclerosis obliterans. [8][9][10][11] In this study we examined how NIRS of the buttocks might reflect changes in the arterial flow of the pelvic area during aortic surgery, and tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Visible light spectroscopy (VLS) appears to be similar to NIRS on some counts [81] with its mean VLS StO2 shown to be not significantly different from NIRS StO2 reported in human studies [67][68][69][70][71][72][73][74][75][76]. Again, the fractional contribution of venous blood to the cerebral NIRS signal has been reported to be 0.84 ± 0.21 ranging from 0.60 to 1.00 [82][83][84].…”
Section: Visible Light Spectroscopymentioning
confidence: 90%
See 1 more Smart Citation
“…Visible light spectroscopy (VLS) appears to be similar to NIRS on some counts [81] with its mean VLS StO2 shown to be not significantly different from NIRS StO2 reported in human studies [67][68][69][70][71][72][73][74][75][76]. Again, the fractional contribution of venous blood to the cerebral NIRS signal has been reported to be 0.84 ± 0.21 ranging from 0.60 to 1.00 [82][83][84].…”
Section: Visible Light Spectroscopymentioning
confidence: 90%
“…In the search for noninvasive, continuous modalities for monitoring ischemia, electrical bioimpedance cardiac output monitoring has been proposed but shown to be incompatible with the thermodilution methods [65,66]. Again, while near-infrared spectroscopy (NIRS) [67] is shown to respond to both hypoxemia [68,69] and ischemia [70][71][72], its clinical use has been limited to large organs, such as the brain [73,74,[85][86][87] with its broad normal ranges reported to be between 48% and 88% [75,76]. Similarly, wide normal ranges are reported for sublingual capnography [77][78][79].…”
Section: Visible Light Spectroscopymentioning
confidence: 99%
“…Rigg et al (10) demonstrated changes in regional cerebral oxygenation associated with retrograde cerebral perfusion on cardiopulmonary bypass. Others have shown that changes in rSO 2 track changes in perfusion of the liver, calf muscles during aerobic exercise, gluteal muscle and visceral perfusion during abdominal aortic surgery (11–13). Hoffman et al (9) have suggested that the two‐site rSO 2 monitoring in pediatric patients undergoing the Norwood procedure may provide important trend information about two differentially controlled vascular beds.…”
Section: Discussionmentioning
confidence: 99%
“…Rigg et al (10) demonstrated changes in regional cerebral oxygenation associated with retrograde cerebral perfusion on cardiopulmonary bypass. Others have shown that changes in rSO 2 track changes in perfusion of the liver, calf muscles during aerobic exercise, gluteal muscle and visceral perfusion during abdominal aortic surgery (11)(12)(13).…”
Section: Figurementioning
confidence: 99%
“…Thallium scintigraphy has been shown to be accurate in detecting exercise-related ischemia in the lower limb, but it is expensive, technically demanding and thus cannot be used as a routine investigation. The recent development of near infrared spectroscopy (NIRS) is promising and seems to be efficient in detecting ischemia at both the buttock 17,25 and ankle level. 26 Nevertheless, its validation against 'gold-standard' arteriography in large groups has not yet been performed.…”
Section: 11à13mentioning
confidence: 99%